Improving weed control in sustainable agro-ecosystems: Role of cultivar and termination timing of rye cover crop - Boselli, Roberta; Anders, Nico; Fiorini, Andrea; Ganimede, Cristina; Faccini, Nadia; Marocco, Adriano; Schulz, Margot; Tabaglio, Vincenzo (Italian Journal of Agronomy, 2021)
Alternative strategies to control weeds are required at the field level to reduce herbicides and derived pollution. As cover crop, rye (Secale cereale L.) is adopted mainly because of its allelopathic weed control, which takes place through a strong inhibition of germination and seedling growth in several types of grass and broad-leaved weeds. The present study consisted of: i) a field trial, focused on the evaluation of biomass production and allelochemical concentration in the biomass, and in situ weed control at 30 days after termination (with two termination timings: T1 - heading phase and T2 - 10 days later) of 8 rye varieties; ii) a pot experiment, focused on the inhibition effect of mulches derived by those 8 rye varieties on four summer weeds: velvetleaf (Abutilon theophrasti Med.), lambsquarters (Chenopodium album L.), redroot pigweed (Amaranthus retroflexus L.), and common purslane (Portulaca oleracea L). Results showed that biomass production was the highest with Protector, closely followed by Primizia, Sito 70, Hellvus, Forestal, and Hymonta. In any case, rye mulching always reduced the weed biomass, especially with Fasto and Forestal. The allelochemical concentration in the biomass was the highest with Fasto and Forestal and decreased on average from T1 to T2 (–38% for total benzoxazinoids and –57% for isovitexin). Conversely, the rye biomass production increased (on average +77%), passing from T1 to T2. We also found that the reduction of weed biomass, compared with the control, is highly correlated with the allelochemical content in rye biomass in the case of T1 termination, while with the biomass production in the case of T2. In pots, a strong inhibitory effect on seedling growth due to rye mulching was observed for C. album (–76%), A. retroflexus (–56%), and P. olearcea (–84%), while not for A. theophrasti. We concluded that, regardless of the variety, adopting rye as a cover crop may be considered as a suitable practice to reduce weed pressure at the field level. Among all the varieties tested, Forestal and Protector showed the most significant weed suppression potential, due to the high amount of allelochemicals production for Forestal and high biomass production for Protector. Highlights - One month after rye termination, the weed biomass under mulching is reduced by 4 times, compared with the control. - When rye is terminated early, the allelochemical content in rye tissues reduces the weed biomass production. - When rye is terminated late, the weed biomass production is reduced by the amount of rye biomass. - Lambsquarters, redroot pigweed and purslane growth is inhibited by rye mulching, while velvetleaf is not affected.